2015
DOI: 10.1038/ncb3194
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive pannexin-1 channels mediate microvascular metastatic cell survival

Abstract: During metastatic progression, circulating cancer cells become lodged within the microvasculature of end-organs, where a majority die from mechanical deformation. Though this phenomenon was first described over a half-century ago, the mechanisms enabling certain cells to survive this metastasis-suppressive barrier remain unknown. By applying whole-transcriptome RNA-sequencing (RNA-seq) technology to isogenic cancer cells of differing metastatic capacity, we identified a mutation encoding a truncated form of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
166
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 50 publications
5
166
1
1
Order By: Relevance
“…In addition to their role in nucleotide release from apoptotic cells, the pannexin channels are also involved in regulating the integrity of the dying cells, 63 regulation of vascular constriction via nucleotides released by non-apoptotic mechanisms, 64 and cancer cell migration. 65 Owing to the ubiquitous expression 66 and vast regulatory mechanisms of Panx1 activation, 61,67 novel cell-type-specific knock-out and transgenic mice affecting apoptosis-specific activation may be necessary to understand its involvement during cell clearance in vivo. Numerous knock-out studies have been performed on other proteins involved in different aspects of these attraction signals.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…In addition to their role in nucleotide release from apoptotic cells, the pannexin channels are also involved in regulating the integrity of the dying cells, 63 regulation of vascular constriction via nucleotides released by non-apoptotic mechanisms, 64 and cancer cell migration. 65 Owing to the ubiquitous expression 66 and vast regulatory mechanisms of Panx1 activation, 61,67 novel cell-type-specific knock-out and transgenic mice affecting apoptosis-specific activation may be necessary to understand its involvement during cell clearance in vivo. Numerous knock-out studies have been performed on other proteins involved in different aspects of these attraction signals.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…Additionally, carbenoxolone (CBX), a Panx-1 inhibitor, was proved to reduce the efficiency of breast cancer metastasis. These results suggested that Panx-1 is one of the molecular bases for metastatic cell survival in microvasculature-induced biomechanical trauma [1]. In 2000, three members of pannexins, including Panx-1, Panx-2, and Panx-3, have been found to be new members of gap-junctions' family [2].…”
mentioning
confidence: 99%
“…However, the roles of ATP in cancer cell death or survival are controversial. Furlow et al [1] found that ATP release from Panx-1 channels activated P2Y-purinergic receptors then promoted cancer cell survival. Moreover, metastasis cell viability was markedly reduced after exposure to the ATP hydrolase [19].…”
mentioning
confidence: 99%
See 2 more Smart Citations